Specific erythrocyte binding capacity and biological activity of Plasmodium falciparum erythrocyte binding ligand 1 (EBL-1)-derived peptides (2005)
Erythrocyte binding ligand 1 (EBL-1) is a member of the ebl multigene family involved in Plasmodiumfalciparum invasion of erythrocytes. We found that five EBL-1 high-activity binding peptides (HABPs)bound specifically to erythrocytes: 29895 (41HKKKSGELNNNKSGILRSTY60), 29903 (201LYECGK-KIKEMKWICTDNQF220), 29923 (601CNAILGSYADIGDIVRGLDV620), 29924(621WRDINTNKLSEK-FQKIFMGGY640), and 30018 (2481LEDIINLSKKKKKSINDTSFY2500). We also show that binding wassaturable, not sialic acid-dependent, and that all peptides specifically bound to a 36-kDa protein on theerythrocyte membrane. The five HABPs inhibited in vitro merozoite invasion depending on the peptideconcentration used, suggesting their possible role in the invasion process.